Assessment and Zoning of Groundwater Quality in Agricultural Areas of Mehran and Dehloran With Geostatistical Methods - FAtemeh Mohammad Yari; Morteza Tvakoli; Hossien Aghdar (علوم و مهندسی آبیاری, 2016)
In this research, chemical properties of groundwater of Mehran and Dehloran areas was considered by using of geostatistical analysis. For this purpose, 29 groundwater samples were studied from 2001 to 2014 and the water conductivity and sodium adsorption ratio were chemically analyzed. Semi variogram of parameters was computed by GS+ software and were fitted by Goussian, sphrical, Expotential and Goussian models. The results showed that the spatial structure of qualitative data of groundwater in these region is reconciled the Gaussian model. Then, using of Arc GIS 10.3 software the Kriging interpolation, inverse distance weighted and Radial basis function methods were done. to select the appropriate model to fit the experimental variogram of the RMSE were used less and more stronger spatial structure. The results of kriging with Inverse distance weighted and radial basis functions using the RMSE and ME RDF Criteria which measure the accuracy rate, were evaluated. Eventually the results of calculating the RMSE and ME showed that kriging method is superior than two other methods and has high precision and low error.so Interpolation was done using this method. In the end, using fuzzy logic, WILCOX classification and WHO classification, zoning map of the study area, for agriculture were prepared. Then Hot spot analysis were used to illustrate the spatial concentration of elements. According to the final map, 38% groundwater of the region is appropriate and sort of appropriate for agriculture and 62% is inappropriate. So can be said that water quality of the study area is not appropriate for agriculture.